AIDS, the second decade - Miller, Heather G.; Turner, Charles F.; Moses, Lincoln E.; National Research Council (U.S.). Committee on AIDS Research and the Behavioral, Social, and Statistical Sciences (Washington, D.C. : National Academy Press, 1990)
Expanding on the 1989 National Research Council volume AIDS, Sexual Behavior, and Intravenous Drug Use, this book reports on changing patterns in the distribution of cases and the results of intervention efforts under way. It focuses on two important subpopulations that are becoming more and more at risk: adolescents and women. The committee also reviews strategies to protect blood supplies and to improve the quality of surveys used in AIDS research. AIDS: The Second Decade updates trends in AIDS cases and HIV infection among the homosexual community, intravenous drug users, women, minorities, and other groups; presents an overview of a wide range of behavioral intervention strategies directed at specific groups; discusses discrimination against people with AIDS and HIV infection; and presents available data on the proportion of teenagers engaging in the behaviors that can transmit the virus and on female prostitutes and HIV infection.
The AIDS epidemic in the second decade -- Prevention : the continuing challenge -- AIDS and adolescents -- Interventions for female prostitutes -- AIDS and the blood supply -- Metholodological issues in AIDS surveys.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: AIDS (Disease) -- United States; AIDS (Disease); Acquired Immunodeficiency Syndrome; Sida -- États-Unis.; Sida; MEDICAL -- AIDS & HIV; HEALTH & FITNESS -- Diseases -- AIDS & HIV; AIDS (Disease); United States; Syndrome d'immunodéficience acquise; Aids; Epidemiologie; Prävention; USA; HIV/AIDS.; AIDS (Disease) -- United States; AIDS (Disease) -- United States -- Prevention; Acquired Immunodeficiency Syndrome; Government Publications, Federal; Internet Resources